Ras/Mitogen-Activated Protein Kinase Signaling Activates Ets-1 and Ets-2 by CBP/p300 Recruitment - Foulds, Charles E. (American Society for Microbiology, 2004)
Cell signaling affects gene expression by regulating the activity of transcription factors. Here, we report that mitogen-activated protein kinase (MAPK) phosphorylation of Ets-1 and Ets-2, at a conserved site N terminal to their Pointed (PNT) domains, resulted in enhanced transactivation by preferential recruitment of the coactivators CREB binding protein (CBP) and p300. We discovered this phosphorylation-augmented interaction in an unbiased affinity chromatography screen of HeLa nuclear extracts by using either mock-treated or ERK2-phosphorylated ETS proteins as ligands. Binding between purified proteins demonstrated a direct interaction. Both the phosphoacceptor site, which lies in an unstructured region, and the PNT domain were required for the interaction. Minimal regions that were competent for induced CBP/p300 binding in vitro also supported MAPK-enhanced transcription in vivo. CBP coexpression potentiated MEK1-stimulated Ets-2 transactivation of promoters with Ras-responsive elements. Furthermore, CBP and Ets-2 interacted in a phosphorylation-enhanced manner in vivo. This study describes a distinctive interface for a transcription factor-coactivator complex and demonstrates a functional role for inducible CBP/p300 binding. In addition, our findings decipher the mechanistic link between Ras/MAPK signaling and two specific transcription factors that are relevant to both normal development and tumorigenesis.